A new professionalism for agricultural research for development - Douthwaite, Boru; Apgar, J.M.; Schwarz, Anne-Maree; Attwood, S.; Senaratna Sellamuttu, Sonali; Clayton, T. (Informa UK Limited, 2017)
There have been repeated calls for a ‘new professionalism’ for carrying out agricultural research for development since the 1990s. At the centre of these calls is a recognition that for agricultural research to support the capacities required to face global patterns of change and their implications on rural livelihoods, requires a more systemic, learning focused and reflexive practice that bridges epistemologies and methodologies. In this paper, we share learning from efforts to mainstream such an approach through a large, multi-partner CGIAR research program working in aquatic agricultural systems. We reflect on four years of implementing research in development (RinD), the program’s approach to the new professionalism. We highlight successes and challenges and describe the key characteristics that define the approach. We conclude it is possible to build a program on a broader approach that embraces multidisciplinarity and engages with stakeholders in social-ecological systems. Our experience also suggests caution is required to ensure there is the time, space and appropriate evaluation methodologies in place to appreciate outcomes different to those to which conventional agricultural research aspires.